Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar IPA Materi Peristiwa Alam Pada Siswa Kelas V SD Negeri 105364 Lubuk Rotan - Wanda Febriana, Umar Darwis (Center of Knowledge : Jurnal Pendidikan Dan Pengabdian Masyarakat, 2022)
This study is a quantitative study that aims to determine the effect of the Problem Based Learning learning model on the science learning outcomes of natural events in the fifth grade students of SD Negeri 105364 Lubuk Rattan. This type of research is a quasi-experimental design using a nonequivalent control group design. The population in this study were all fifth grade students of SD Negeri 104275 Lubuk Saban for the 2020/2021 academic year. The population consists of two classes, namely parallel class with 38 students. There are 20 students in class VA and 38 students in VB. The technique of collecting data on learning outcomes used multiple choice tests and data on learning outcomes were analyzed by t-test. The results of the study indicate that the learning outcomes of students who use the Problem Based Learning model are greater than the learning outcomes of students who use conventional learning models. The average post-test value in the control class is 59.72 while the average post-test value in the experimental class is 80. The t-test results show the value of tcount (5.76) > ttable (1.68), then Ha is accepted and H0 is rejected. Therefore, there is a significant effect on the application of the mind mapping learning model in the VA class compared to the conventional learning model in the VB class. This proves that the Problem Based Learning learning model has an effect on improving science learning outcomes for natural events in fifth grade students of SD Negeri 105364 Lubuk Rattan.